A generic cell surface ligand system for studying cell-cell recognition. - Eleanor M Denham; Michael I Barton; Susannah M Black; Marcus J Bridge; Ben de Wet; Rachel L Paterson; P Anton van der Merwe; Jesse Goyette (PLoS Biology)
Dose-response experiments are a mainstay of receptor biology studies and can reveal valuable insights into receptor function. Such studies of receptors that bind cell surface ligands are currently limited by the difficulty in manipulating the surface density of ligands at a cell-cell interface. Here, we describe a generic cell surface ligand system that allows precise manipulation of cell surface ligand densities over several orders of magnitude. These densities are robustly quantifiable, a major advance over previous studies. We validate the system for a range of immunoreceptors, including the T-cell receptor (TCR), and show that this generic ligand stimulates via the TCR at a similar surface density as its native ligand. We also extend our work to the activation of chimeric antigen receptors. This novel system allows the effect of varying the surface density, valency, dimensions, and affinity of the ligand to be investigated. It can be readily broadened to other receptor-cell surface ligand interactions and will facilitate investigation into the activation of, and signal integration between, cell surface receptors.